Benchbook on international law - Amann, Diane Marie (The American Society of International Law, 2014)
"This Benchbook provides a hands-on introduction to international law as it arises in courts of the United States. Its primary audience will be U.S. District Judges, typically the first to encounter questions of international law in our system ... the Benchbook begins with a primer on international law's sources and status in U.S. courts. Jurisdictional, preliminary, and procedural concerns, like immunities and evidence-gathering, next are treated. The Benchbook then provides discussions of concrete instances in which such issues may arise; for example, arbitration, child abduction, human rights, and the international sale of goods. It concludes with issues of interpretation and research resources."--Preface